Integrated TR-069 and MikroTik Automation for ISP Network Provisioning: A Case Study of PT Mahakam Indo Nusa - Asep Nurhuda; Muslimin B; Bagus Satria; Reza Jakaria Rahmanto; Eny Maria (Poltanesa, 2025)
PT Mahakam Indo Nusa is a new internet service provider facing challenges in managing Customer Premises Equipment (CPE) and PPPoE-based network authentication on MikroTik Routers. The existing manual process slows down service and is prone to configuration errors. This research develops a Laravel-Vue based Posmacs application that integrates GenieACS (a TR-069 implementation) with the MikroTik API. The objective of the research is to automate the provisioning process, CPE configuration, and device status monitoring. The research uses the Design Science Research (DSR) approach with six stages: problem identification, solution objective, design and development, demonstration, evaluation, and communication. The implementation results show that the Posmacs application is capable of retrieving data for thousands of devices from GenieACS with a pagination system, automatically connecting new customers with MikroTik PPPoE accounts, and displaying online/offline device status via a dashboard. This application enhances the operational efficiency of PT Mahakam Indo Nusa as a new ISP.